Strengthening Literacy Read Write Count (Sicalistung) For Children of Yeflio Tourism Village - Setyo, Arie Anang; Layn, Muhamad Ruslan; Trisnawati, Nika Fetria; Sundari, Sundari; Heriyanti, Heriyanti; Lestari, Badiana Adil (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this service activity is toincreasing interest in reading, enthusiasm for learning, understanding in recognizing letters and improving the reading and counting skills of the Yeflio village children. This activity was carried out in Yeflio village, Mayamuk District, Sorong Regency, Southwest Papua Province. Participants who took part in this community service activity were children of pre-school age, elementary school age, and junior high school. Participants in this community service activity totaled 50 children, with 33 girls and 27 boys. The implementation of this activity was carried out using several reading guidebooks and arithmetic books as well as reading, writing and arithmetic learning media that were made. The activities were carried out for 16 meetings from 23 August to 15 September 2022 every Monday to Thursday at 15.00. 00 to 17.00 WIT. The learning process is carried out both classically and in groups according to the abilities of the participants. Data collection was carried out by means of observation and tests, data on the results of activities were analyzed using descriptive statistics. The results of the community service activities concluded that there was an increase in literacy skills in reading, writing, arithmetic (SICALISTUNG) in activity participants with details of an increase in the number of participants who already knew letters by 4 out of 8 participants or 8%, and fluent reading by 16 people or 32%. In writing literacy, the increase occurred in participants who wrote fluently by 4 people (16.7%) and participants who could not write decreased to only 1 person out of 6 people or 8.3%. In the numeracy literacy program there was also an increase in the average score from 14 to 42 in the addition and subtraction program.